The Implementation of a Sustainable Food and Agricultural Land Protection Policy in Pringsewu District - Sormin, Rahma Diani (Universitas Terbuka, 2024)
The development in Pringsewu District is currently being monitored at a rapid pace, with the function of rice field land being reactivated as a growing land. The increasing population and growing needs of the community present a significant threat to the continued existence of productive rice fields. Pringsewu District is an urban area where the majority of existing land has the potential to be transformed into agricultural land. This phenomenon presents an intriguing case study for examining the implementation of regional regulations in Pringsewu Regency, specifically Regulation Number 6 of 2015 regarding the sustainable protection of food farming land. The research method employs a descriptive qualitative approach, utilizing data collection techniques such as interviews, observations, and documentation. The implementation of Regional Regulation No. 6 of 2015 regarding the protection of sustainable food farming land has not been effectively carried out. This is due to a lack of public awareness concerning the significance of sustainable food agricultural land. Despite the challenges inherent in implementing Local Regulation No. 6 of 2015 on sustainable food farm protection, the Pringsewu district government has consistently endeavored to ensure that the development of Pringsewu regency is guided by Local Regulation No. 6 of 2015 on sustainable food agricultural land protection. This approach is designed to facilitate a harmonious relationship between development and the environment. Keywords: food farming, implementation, regulation, sustainable.